MULTIFRACTAL STRUCTURE OF THE LATERAL DISTRIBUTION OF SEISMICITY - Geylikman M.B.; Golubeva T.V.; Pisarenko V.F. (My University, 1990)
Investigation of the lateral distribution of seismicity has identified a self-similar hierarchical structure in the seismic field. In addition, it has been shown that the clustering of weak earthquake in plan is of predictive value. It thus becomes imperative to identify the most realistic and detailed method for analysis of the structure of seismicity. To overcome various applications difficulties, Halsey et al. recently proposed a multifractal approach, in which the entire dimensionality spectrum of the given set is considered. In the present paper use the multifractal approach to investigate the lateral distribution of earthquake epicenters. The method is, of course, also applicable to other geophysical fields.